2014
DOI: 10.1371/journal.pone.0105684
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 and Human β2-Microglobulin Affect the Gut Microbiota of Transgenic Rats

Abstract: The HLA-B27 gene is a major risk factor for clinical diseases including ankylosing spondylitis, acute anterior uveitis, reactive arthritis, and psoriatic arthritis, but its mechanism of risk enhancement is not completely understood. The gut microbiome has recently been shown to influence several HLA-linked diseases. However, the role of HLA-B27 in shaping the gut microbiome has not been previously investigated. In this study, we characterize the differences in the gut microbiota mediated by the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(177 citation statements)
references
References 54 publications
11
164
0
2
Order By: Relevance
“…For example, in AS there is evidence of gut microbiome dysbiosis with an abundance of the genus Dialister correlated with disease activity [35]. Supporting this information, Lin et al [36] showed that the gut microbiota is different in HLA-B*27 transgenic mice compared with wild-type mice, showing a correlation between possession of HLA-B*27 and the shaping of the gut microbiome. In patients with skin psoriasis and PsA a recent study found that the diversity of the gut microbiome was lower compared to healthy controls, due to a lower abundance of several taxa [37].…”
Section: Microbiome Involvementmentioning
confidence: 93%
“…For example, in AS there is evidence of gut microbiome dysbiosis with an abundance of the genus Dialister correlated with disease activity [35]. Supporting this information, Lin et al [36] showed that the gut microbiota is different in HLA-B*27 transgenic mice compared with wild-type mice, showing a correlation between possession of HLA-B*27 and the shaping of the gut microbiome. In patients with skin psoriasis and PsA a recent study found that the diversity of the gut microbiome was lower compared to healthy controls, due to a lower abundance of several taxa [37].…”
Section: Microbiome Involvementmentioning
confidence: 93%
“…Другой важный аспект этой проблемы связан с ро-лью кишечного воспаления в патогенезе СпА [58][59][60]. По данным экспериментальных исследований, у «транс-генных» мышей, несущих гены HLA-B27 и β2-микрогло-булина, отмечается развитие воспаления кишечника, коррелирующее с увеличением экспрессии ИЛ12 и ИЛ17 в воспаленной ткани [61,62]. Установлено нарушение кишечной микробиоты у трансгенных HLA-B27 крыс по сравнению с диким типом [63].…”
Section: таблицаunclassified
“…Intestinal dysbiosis is now being understood as a major cause of dysregulated immunity in Ax SpA. Diversity in the intestinal microbiome may alter immunogenetic and epigenetic factors that confer risk for this disease [13,14].…”
Section: Environmental Risk Factors: Microbial and Gut Influences?mentioning
confidence: 99%